Research Paper: Sex Identification by Morphometric Study of Hyoid Bone - Okasi, Arash; Sadeghian, Mohammad Hossein; Behnoush, Behnam; Shakori Rad, Ali (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Morphometric measurements are important for identification in forensic medicine. Gender is one of the important components of identity. Many studies have reported that hyoid bone can be used for sex estimation but this claim must be verified in different populations. Methods: We evaluated 372 hyoid bones of 15 to 87 years old Iranian people who had a valid identity certification. Nine anthropometric indices of hyoid bone were measured and investigated in this regard. Computerized tomography scan was done after fixation of dissected tissue in formalin. Logistic regression analysis was performed. The cut-off point (ROC) and discriminative formula were determined. Results: In this study, hyoid bones of Iranian bodies were studied, of which 217 were male and 155 were female cases. The length of the hyoid body, great left horn length, angle between right great horn and left great horn with body of hyoid are associated with sex determination. Conclusion: Hyoid bone in male is generally larger than in females. The result indicate that the hyoid bone morphometry with a high degree of accuracy can determine the sex. Discriminant formula was determined for hyoid bone.